Screening Study for Anticonvulsive Activity of Lipophilic Fractions from Empetrum nigrum L. - Ekaterina A. Bezverkhniaia; Tatyana N. Povet'eva; Tatyana V. Kadyrova; Nikolai I. Suslov; Yuliya V. Nesterova; Ol'ga G. Afanas'eva; Pavel V. Kul'pin; Yuliya G. Yusova; Elena V. Ermilova; Alexandr G. Miroshnichenko; Konstantin S. Brazovskii; Mikhail V. Belousov (Belgorod National Research University, 2020)
Introduction: The plants of genus Empetrum, which are used in the traditional medicine to cure seizures and neurodegenerative diseases, can be considered as potent antiepileptic drugs. This paper focuses on a comparative analysis of an anticonvulsive activity of lipophilic fractions from Empetrum nigrum L. Materials and methods: The experiments were conducted using mature outbred CD-1 male mice. The lipophilic fractions from aerial parts of Empetrum nigrum L. were administered through a catheter into the stomach at a dose of 150 mg/kg for 5 days. The anticonvulsive effects were studied using the acute seizure tests: strychnine-, pentylenetetrazole - and maximal electroshock (MES) induced tests. Carbamazepine was used as a positive control drug at a dose of 100 mg/kg. Results and discussion: The acetone-soluble fraction (ASF) of the chloroform extract from Empetrum nigrum L. showed a pronounced anticonvulsive effect on seizures induced by strychnine (1.5 mg/kg) and pentylenetetrazole (150 mg/kg). In comparison to the control group, the time from seizures to death increased by 1.5 for the strychnine-induced seizures, and 1.9 times in case of pentylenetetrazole model. The survival rate of the animals was 22.2% and 20%, correspondingly. The survival rate in the MES test was 77.8%. Overall, ASF demonstrates a remarkable anticonvulsive activity in all the tests, especially in the MES test. Conclusion: Our study for the first time shows a potent antiepileptic effect of ASF from Empetrum nigrum L., containing triterpene compounds and chalcones. The future studies will be focused on investigating the exact mechanisms of anticonvulsive and neuroprotective effects of ASF. Graphical abstract